1990
DOI: 10.1002/bip.360300310
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure effects on the interaction of different polynucleotides with Ca2+

Abstract: School for Advanced Studies, 1-341 27 Trieste, and 31nstitute of Biology, University of Udine, 1-331 00 Udine, Italy SYNOPSISThe interaction of Ca2+ ions in 10 m M NaCl at 17OC with polynucleotides of different primary and secondary structure has been investigated. The experimental results show the following:1. The affinity for calcium ion depends on the secondary structure of the polynucleotide and not, within the experimental error, on the base sequence.2. The following hierarchy in calcium ion binding can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In the former paper (Langlais et al, 1990), Raman spectroscopy shows that Mg 2ϩ and Ca 2ϩ interact dominantly with charged phosphates and very little with the bases. The other study shows that Ca 2ϩ binding to DNA is independent of base sequence and can be interpreted by polyelectrolyte theory (Manzini et al, 1990). Our data of Ca 2ϩ binding to the DNA fragments (Li et al, 1997) is well interpreted by Manning's CC theory, which includes only phosphate interactions, thus supporting the above obervation.…”
Section: Metal Cation Typesupporting
confidence: 83%
See 4 more Smart Citations
“…In the former paper (Langlais et al, 1990), Raman spectroscopy shows that Mg 2ϩ and Ca 2ϩ interact dominantly with charged phosphates and very little with the bases. The other study shows that Ca 2ϩ binding to DNA is independent of base sequence and can be interpreted by polyelectrolyte theory (Manzini et al, 1990). Our data of Ca 2ϩ binding to the DNA fragments (Li et al, 1997) is well interpreted by Manning's CC theory, which includes only phosphate interactions, thus supporting the above obervation.…”
Section: Metal Cation Typesupporting
confidence: 83%
“…The result is not surprising, because quite a few studies (Eichhorn and Shin, 1968;Daune, 1974;Langlais et al, 1990;Manzini et al, 1990;Re, 1991;Duguid et al, 1993Duguid et al, , 1995 showed that alkaline earth metal cations and transition metal cations have different mechanisms of interacting with and binding to double-stranded DNA. From previous studies (Langlais et al, 1990;Manzini et al, 1990) it was concluded that alkaline earth cations interact primarily with DNA phosphates, resulting in stabilization of the double helix via reduction of electrostatic repulsion. In the former paper (Langlais et al, 1990), Raman spectroscopy shows that Mg 2ϩ and Ca 2ϩ interact dominantly with charged phosphates and very little with the bases.…”
Section: Metal Cation Typementioning
confidence: 98%
See 3 more Smart Citations